Knowledge Distillation for COVID-19 Therapeutics - Zhai, Shiyao; Gao, Yuhan; Peng, Kailai; Chen, Qun; He, Qian; Fang, Li; Li, Linling; Zhong, Bowen; Dong, Yuhan; Yan, Chenggang; et al. (Archives of Clinical and Biomedical Research, 2022)
The novel coronavirus disease (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 is threatening the world's economy and healthcare with urgent therapeutic demand. Clinical and scientific studies have made promising progress in ameliorating and treating COVID-19. The unprecedented effort has brought several vaccines approved for emergency use, and prevalent vaccination is advocated globally. However, methods that can effectively clear the virus and terminate transmission are not available. The variants and uncontrolled circulations bring persistent challenges for therapeutics and vaccines. In this review, we discuss the ongoing treatments, the mechanism, and potential optimization of various therapeutics. We review the viral pathogenesis and epidemiology and provide insights for prospective therapeutics and vaccine evolution, which will help clinical doctors and researchers in this pandemic.